'Green' composites prepared from polyfurfuryl alcohol and cork residues: Thermal and mechanical properties - Menager, Charlotte; Guigo, Nathanael; Wu, Xuan; Vincent, Luc; Sbirrazzuoli, Nicolas (Composites science and technology, 2019)
Polyfurfuryl alcohol (PFA) is a biobased thermoset like matrix with high thermal performances and cork powder or cork granules are side stream product from cork stoppers’ production. They were processed together via compression molding. Structural investigations were made by means of FT-IR and thermo-mechanical measurements were performed using tensile tests, thermogravimetric analyses (TGA) and dynamic mechanical analyses (DMA). The fracture surface morphology controlled by scanning electronic microscopy (SEM) shows that cork cells are well filled by PFA and that homogeneous composites can be formed. The addition of PFA allows increasing sharply the elastic modulus and the tensile strength which attest for good adhesion between PFA and cork. The thermal degradation of cork/PFA composites is shifted to higher temperature (±20 °C) which indicates that PFA helps to prevent the cork decomposition. Finally PFA reduce significantly the absorption of water in composites.